Ageing and cancer: a research gap to fill. Issue 18 (21st May 2022) - Solary, Eric; Abou‐Zeid, Nancy; Calvo, Fabien
Abstract : The complex mechanisms of ageing biology are increasingly understood. Interventions to reduce or delay ageing‐associated diseases are emerging. Cancer is one of the diseases promoted by tissue ageing. A clockwise mutational signature is identified in many tumours. Ageing might be a modifiable cancer risk factor. To reduce the incidence of ageing‐related cancer and to detect the disease at earlier stages, we need to understand better the links between ageing and tumours. When a cancer is established, geriatric assessment and measures of biological age might help to generate evidence‐based therapeutic recommendations. In this approach, patients and caregivers would include the respective weight to give to the quality of life and survival in the therapeutic choices. The increasing burden of cancer in older patients requires new generations of researchers and geriatric oncologists to be trained, to properly address disease complexity in a multidisciplinary manner, and to reduce health inequities in this population of patients. In this review, we propose a series of research challenges to tackle in the next few years to better prevent, detect and treat cancer in older patients while preserving their quality of life. Abstract : The complex mechanisms that cause ageing can generate multiple late‐onset diseases, including cancer. Recently, several mechanistic links between ageing and cancer have been reported. In order to complete geriatric assessment and guide therapeutic choices in elderly patients with cancer, biological measurement of the effects of ageing has been proposed. This review explores multiple remaining issues to be addressed in an effort to improve cancer care in elderly patients.